Inherited glycosylphosphatidylinositol deficiency disorders: a new group of inherited metabolic disorders - Michał Patalan; Alicja Leśniak; Justyna Paprocka; Agnieszka Zubkiewicz-Kucharska; Kaja Giżewska-Kacprzak; Marta Glińska; Lidia Babiak-Choroszczak; Maria Giżewska; Robert Śmigiel (Pediatria Polska)
Inherited glycosylphosphatidylinositol deficiency disorders (IGDs) are a group of rare congenital disorders of glycosylation with multisystemic involvement. The underlying cause is an abnormal structure of glycosylphosphatidylinositol, which plays a significant role in the attachment of proteins to the cellular membrane. These glycosylphosphatidylinositol-anchored proteins are an important part of receptors, function as hydrolytic enzymes, and play a crucial role in molecules adhesion, immune response, embryogenesis and neurogenesis. Patients present a variety of symptoms including developmental delay with intellectual disability, abnormalities of the central nervous, skeletal, circulatory, gastrointestinal, and urinary systems, facial dysmorphia as well as hearing and visual impairment. Elevated alkaline phosphatase is a characteristic biochemical feature. The current state of knowledge connects the highly differentiated course of clinical presentation with the heterogenic molecular background evaluated in the next-generation sequencing methods. We present a comprehensive review of the pathogenesis, clinical symptomatology and management options in IGDs.